PENGARUH PENGAWASAN TERHADAP EFISIENSI KERJA PEGAWAI PADA DINAS LINGKUNGAN HIDUP KABUPATEN TAPANULI TENGAH - Nadzran, Nadzran; Adinata Ginting, Juah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The purpose of the research carried out in completing this thesis is to find out the extent of the effect of Supervision on the Work Efficiency of Employees at the Environmental Office of Central Tapanuli Regency. From the results of research conducted note that the effect of Supervision on Employee Work Efficiency is strong, where the calculation of Product Moment correlation is obtained 0.784 or strong correlation. As the linear regression calculation of the equation Y = a + bX obtained Y = 10,528 + 0.722X. In this case the work efficiency of employees will be increased by carrying out proper supervision. Furthermore, the magnitude of the effect of supervision on employee work efficiency is determined by the coefficient of determination that is equal to 0.615 or 61.5%. This means that the contribution of variable X (Oversight) to the Y variable (Work Efficiency) is 61.5%, while the remaining 38.5% is determined by other factors not discussed by the authors in this study, but requires further research to prove it. From the hypothesis test conducted and by comparing the value of tcount and ttable, it is found that the tcount value (7.776) is greater than the ttable value (2.024) or 7.776> 2, 024, thus based on the results of the study and the results of the research discussion, the proposed hypothesis in Chapter I namely that there is an influence of supervision on the work efficiency of employees at the Central Tapanuli Regency Office of Environment, its truth is acceptable.